Daylighting performance analysis of a facade combining daylight-redirecting window film and automated roller shade. (15th March 2021) - Do, Cong Thanh; Chan, Ying-Chieh
Abstract: Daylighting provides a wide range of benefits for buildings and occupants, including light energy saving and a direct connection to the outdoors. Excessive sunlight can be eliminated using automatically controlled roller shades, and distribution can be improved by sending light to the back of a room using daylight redirecting films. These technologies can be combined in a multi-sectional facade to maximize its potential in serving different functions (light energy saving, glare prevention, and views). This paper aims to evaluate daylight redirecting film's effectiveness when combined with automatically controlled roller shades by analyzing daylight availability, glare prevention, and visibility through the facade. We also aim to provide a guide for designing a multi-sectional facade system. We conducted a parametric study scheme using a workflow based on Radiance's three-phase method. The evaluated design elements included the dimensions of the daylight redirecting film, and the properties of two glazing systems (top and middle sections) and shading fabrics. Besides daylighting availability and glare, we created a view index to evaluate the facade's "see-through" throughout a year. The results indicated that the film-to-wall ratio is the most critical design element in the scheme. An increased glass transmittance in the top section could result in higher daylight availability, while a decreased glass transmittance in the middle section could provide more outdoor views. Finally, we created a multi-sectional facade design guide to help designers understand potential trade-offs between different materials. Highlights: Daylight redirecting film combined with automated roller shades are evaluated. A view index is formed to evaluate occupants' outdoor views. An increase of glass transmittance in the façade's top section increases daylighting. Decreasing glass transmittance in the middle section provides more outdoor views. A guide is developed for designing a multi-sectional facade system.